Correlation between pre-extraction periodontal diagnosis and peri-implant microbiome for patients treated with implant-retained overdenture – A retrospective cohort pilot study - Xiaoxi Cui; Acela A. Martinez Luna; Alex Gillone; Qiang Wu; Mahmoud Serag; Ramiro Mendonca Murata (PLoS ONE, 2025)
Limited clinical data exists on the peri-implant microbiome in edentulous patients with implant-retained overdentures (IRO). This study aimed to examine the peri-implant microbiome and its correlation with pre-treatment periodontal diagnosis. A total of twenty-five patients with 50 implants were included, with demographic information and pre-treatment periodontal diagnosis collected. Clinical measurements and subgingival plaque samples were obtained from each implant, followed by 16S rRNA gene-targeted sequencing. Peri-implant parameters and microbiome were analyzed in relation to gender, remaining teeth prior to treatment, IRO function time, implant system, bone graft at implant placement, and peri-implant diagnosis. The mean age of patients was 71 years, with pre-extraction diagnoses including clinical healthy gingiva on a reduced periodontium (4 patients), localized periodontitis (4 patients), generalized periodontitis (7 patients), and generalized Stage IV Grade C periodontitis (10 patients). Nineteen implants were diagnosed with peri-implant mucositis, while 31 were healthy. The predominant genera detected were Streptococcus, Rothia, Veillonella, Actinomyces, and Schaalia. No significant correlation was found between pre-treatment periodontal diagnosis and peri-implant diagnosis. The findings suggest that while pre-extraction periodontal diagnosis might influence the peri-implant subgingival microbiome in IRO patients, it may not correlate with the clinical peri-implant diagnosis.